Predictive Models of Maternal Harsh Parenting During COVID-19 in China, Italy, and Netherlands - Riem, Madelon M. E.; Lodder, Paul; Guo, Jing; Vrielink-Verpaalen, Michelle; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; De Carli, Pietro (Frontiers in Psychiatry, 2021)
Background. The COVID-19 pandemic drastically impacted on family life and may have caused parental distress, which in turn may result in an overreliance on less effective parenting practices. Objective. The aim of the current study was to identify risk and protective factors associated with impaired parenting during the COVID-19 lockdown. Key factors predicting maternal harsh discipline were examined in China, Italy, and The Netherlands, using a cross-validation approach, with a particular focus on the role of allomaternal support from father and grandparents as a protective factor in predicting maternal harshness. Methods. The sample consisted of 900 Dutch, 641 Italian, and 922 Chinese mothers (age M=36.74, SD=5.58) who completed an online questionnaire during the lockdown. Results. Although marital conflict and psychopathology were shared risk factors predicting maternal harsh parenting in each of the three countries, cross-validation identified a unique risk factor model for each country. In The Netherlands and China, but not in Italy, work-related stressors were considered risk factors. In China, support from father and grandparents for mothers with a young child were protective factors. Conclusions. Our results indicate that the constellation of factors predicting maternal harshness during COVID-19 is not identical across countries, possibly due to cultural variations in support from fathers and grandparents. This information will be valuable for the identification of at-risk families during pandemics. Our findings show that shared childrearing can buffer against risks for harsh parenting during COVID-19. Hence, adopting approaches to build a pandemic-proof community of care may help at-risk parents during future pandemics.